Risk of injury analysis in depth jump and squat jump - Tomasevicz, C. L.; Woldstad, J. C.; Jones, D. D. (Journal of Human Sport & Exercise, 2022)
Introduction: The depth jump (DJ) and squat jump (SJ) are accepted ways to assess and train power producing ability but are not without risk of injury. Methods: Sixteen male participants (age = 21.7 ± 1.54 yrs., height = 177.7 ± 11.4 cm, mass = 77.7 ± 13.6 kg) were evaluated for power exertion capabilities while being assessed for risk of injury in the knee and low back through a range of resistances based on a percentage of participants` heights in the DJ (0% through 50%) and bodyweights for the SJ (0% through 100%). Two variables were used to assess the risk of injury in the knee: valgus angle and internal abduction moment (IAM). Four variables were used in the low back: compression and shear force at the L5/S1 vertebrae, intra-abdominal pressure (IAP), and erector muscle tension. Results: With increasing DJ drop height, participants showed increased risk of injury in the knee through the valgus angle and IAM. In the low back, significant correlation occurred between increasing drop height and the shear force and IAP while compression force and erector muscle tension were more correlated with the power exertion of the participants than the drop height. With increasing SJ resistance, no significant increased risk of knee injury was detected. However, all low back variables except the IAP were significantly influenced by the increased resistance. Conclusion: Risk of injury in the knee and low back can be strongly dependent not only on the type of jump, but also the amount of resistance. The resulting power exerted by the athlete can also influence the risk of injury.